Improving Mathematical Communication Ability and Self Confidence of Junior High School Students Through Learning Transactional Reading Strategy - Suheri, Ukan (Study Program of Mathematics Education University of Muhammadiyah Malang, 2018)
This study is a quasi experiment that aims to determine whether theachievement and improvement of students' mathematical communicationskills and confidence of students who get the Learning TransactionalReading Strategy is better than the ordinary study reviewed overall andKAM categories. Alternative approach applied is Learning TransactionalReading Strategy. The research method used is quasi experimental methodwith the population of junior high school students in Bandung. While thesample is taken from class VII as much as two classes are randomlyselected from 9 classes. Before doing the research the first test ofprerequisite or Early Mathematical Ability (KAM) is done. At thebeginning and end of the learning the two experimental and control classeswere given a test and attitude questionnaire. The data collection in thisresearch is in the form of test which contains 6 description questions formathematical communication ability and 30 attitude questionnaires ofstudent's self confidence .The score data of each capability was analyzed by descriptive andinferential statistic using the difference test of two averages. Based on theresults of the study, both the results of data analysis and hypothesis testing,the author concludes that the improvement of mathematical communicationskills of students who get the learning transactional reading strategy isbetter than the improvement of students' communication skills learningusing ordinary learning reviewed overall and KAM category is medium.While the self-confidence of students who get the learning transactionalreading strategy is better than the students' self-confidence who getordinary learning reviewed overall and categories of high, medium and lowKAM.